You said...
"If a/bc = a/(bc), then a/bc = a/b/c
Which seems nonsensical to me."

In fact that is completely correct - just put some numbers in...
1÷2÷3=(1/2)÷3=1/6=1/(2*3)
In the same way that distributing a minus over a bracketed term changes any + to a -, distributing a ÷ over any bracketed term changes a x to a ÷.
This is a well-known property in Maths which is covered when teaching multiplying and dividing fractions.
Someone once asked me "what is a/b/c/d?". Easy, a/bcd

You said...

"If a/bc = a/(bc), then a/bc = a/b/c

Which seems nonsensical to me."

In fact that is completely correct - just put some numbers in...

1÷2÷3=(1/2)÷3=1/6=1/(2*3)

In the same way that distributing a minus over a bracketed term changes any + to a -, distributing a ÷ over any bracketed term changes a x to a ÷.

This is a well-known property in Maths which is covered when teaching multiplying and dividing fractions.

Someone once asked me "what is a/b/c/d?". Easy, a/bcd